Additive effect of tDCS and neuromotor recruitment on functional recovery in chronic paraplegia: A randomized controlled trial - Ahmad Rifai Sarraj; Jihan Allaw; Eliane Rached; Joy Khayat; Hassan Karaki; Ahmad Diab; Antonio Pinti (PLoS ONE, 2026)
Functional recovery in chronic spinal cord injury (SCI) is traditionally viewed as limited, particularly after the spontaneous recovery window has closed. This single-blind randomized controlled trial investigated whether adding anodal Transcranial Direct Current Stimulation (tDCS) to the Neuromotor Recruitment Method (NEUROM)—a protocol combining motor imagery with intensive peripheral sensory stimulation—provides a additive benefit for sensorimotor recovery. Fifty participants with chronic paraplegia (mean time since injury: 15.4 ± 3.2 months; ASIA Impairment Scale A, B, or C) were recruited and randomized into three arms: Reference (standard care, n = 10), NEUROM (n = 20), or NEUROM+tDCS (n = 20). The intervention was administered over 10 days. Outcomes included the Lower Extremity Motor Score (LEMS), Light Touch and Pin Prick sensory scores, and the Assessment of Movement Attempt (AMA). The Reference group showed no significant recovery. Both active groups (NEUROM and NEUROM+tDCS) achieved substantial and statistically identical improvements in sensory function compared to the Reference group ( p < 0.001), suggesting that peripheral recruitment alone is sufficient for afferent restoration. However, a significant dissociation was observed in motor function: the NEUROM+tDCS group demonstrated superior LEMS recovery (Mean change: 18 points) compared to the NEUROM group (14 points; p = 0.01) and reported significantly higher volitional drive ( p < 0.001). These findings indicate a clear dissociation between sensory and motor plasticity in chronic SCI; while peripheral somatosensory recruitment drives afferent sensory restoration, the addition of central stimulation via tDCS is critical for maximizing efferent motor output. This suggests that restoring motor function in chronic paraplegia requires a “top-down” cortical prime to complement “bottom-up” peripheral signaling. Trial Registration: ClinicalTrials.gov NCT04790149 .